Answer:
After completing the square the expression is (x-2)^2 -12 =0 and real solution are x = 5.46 and x = -1.46
Step-by-step explanation:
We need to complete the square:
x^2 − 4x − 8 = 0
x^2 -2(x)(2)+(2)^2 -8 -4 =0
(x^2 -4x +4) - 12 = 0
(x-2)^2 -12 =0
Now, finding the value of x
(x-2)^2 -12 =0
(x-2)^2 = 12
taking square root on both sides
![\sqrt{(x-2)^2}= \sqrt{12} \\(x-2) = \pm\sqrt{12} \\x = \pm\sqrt{12} +2\\x = \sqrt{12}+2 \,\,and\,\,x=-\sqrt{12}+2\\x= 3.46+2 \,\,and\,\,x=-3.46+2\\x =5.46\,\,and\,\,x=-1.46](https://tex.z-dn.net/?f=%5Csqrt%7B%28x-2%29%5E2%7D%3D%20%5Csqrt%7B12%7D%20%5C%5C%28x-2%29%20%3D%20%5Cpm%5Csqrt%7B12%7D%20%5C%5Cx%20%3D%20%5Cpm%5Csqrt%7B12%7D%20%2B2%5C%5Cx%20%3D%20%5Csqrt%7B12%7D%2B2%20%5C%2C%5C%2Cand%5C%2C%5C%2Cx%3D-%5Csqrt%7B12%7D%2B2%5C%5Cx%3D%203.46%2B2%20%5C%2C%5C%2Cand%5C%2C%5C%2Cx%3D-3.46%2B2%5C%5Cx%20%3D5.46%5C%2C%5C%2Cand%5C%2C%5C%2Cx%3D-1.46)
So, After completing the square the expression is (x-2)^2 -12 =0 and real solution are x = 5.46 and x = -1.46
Answer:
215
Step-by-step explanation:
60=50
258=?
258 divided by 60 = 4.3
50 x 4.3 = 215
First, change the fractions to a common denominator, which is 21.
so 3/7 * 3/3 = 9/21
1/3 * 7/7 = 7/21
Add the two together
9/21 + 7/21 = 16/21
Then take 21/21 - 16/21 = 5/21
There is 5/21 of the pizza left.
Answer:
Answer:- Function
please mark me as brainliest